Monitoring of Temperature Through a Sensor Network to Improve the Water Usage in Agriculture - Aguilar-González, Rafael; Cárdenas-Juárez, Marco; Rodríguez-Ortiz, Juan Carlos; Romero-Méndez, Mauricio Jesús (REVISTA TERRA LATINOAMERICANA, 2023)
Technological trends are present in dif ferent areas, in the case of agriculture, it is possible to find applications such as automated greenhouses. However, for a large part of small producers in countries with conditions like Mexico, this type of technological advance means a dif ficult investment to make. Fortunately, today, it is possible to improve the productivity of the field with af fordable technology. In this work, the development of electronic devices to measure the temperature inside a 1000 m2 greenhouse is described. These sensors have the capability to form a network, with which the temperature of various points within the greenhouse was obtained. The information collected was concentrated on the internet and through an interpolation algorithm, those areas with the highest temperature were determined. This allowed punctual and localized irrigation therefore making water use ef ficient. These research notes are the first part of a project to develop af fordable electronic devices capable of measuring climatic variables such as temperature, relative humidity, and light, among others. With the data obtained, the evapotranspiration coef ficient can be calculated to estimate the amount of water needed in each crop area.